Search for supersymmetry in di-photon final states at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Elsevier B.V., 2008)
We report results of a search for supersymmetry (SUSY) with gauge-mediated symmetry breaking in di-photon events collected by the do experiment at the Fermilab Tevatron Collider in 2002-2006. In 1.1 fb(-1) of data, we find no significant excess beyond the background expected from the standard model and set the most stringent lower limits to date for a standard benchmark model on the lightest neutralino and chargino masses of 125 GeV and 229 GeV, respectively, at 95% confidence. (C) 2007 Elsevier B.V. All rights reserved.